Rapid determination of trace nitrofurantoin in cosmetics by surface enhanced Raman spectroscopy using nanoarrayed hydroxyl polystyrene‐based substrate. (27th May 2019) - Zhang, Yi; Yu, Zhongning; Yue, Zhenfeng; Gao, Jiamin; Wu, Shaojing; Zhang, Zhuomin; Li, Gongke
Abstract: The safety of cosmetics attributing to the illegal addition of antibiotics for quick effect is a big concern nowadays. Nitrofurans, one of commonly added illegal antibiotics, are strictly banned in cosmetics in China. It is still a great challenge for the rapid and precise analysis of trace nitrofurans when facing various cosmetics with complicated matrices. Surface‐enhanced Raman spectroscopy (SERS) is emerging as a novel rapid on‐site analytical technique. In this work, an accurate SERS method was developed for the rapid analysis of trace nitrofurantoin in various cosmetics by use of nanoarrayed hydroxyl polystyrene (PS‐OH)‐based substrate. A series of characterizations indicated the successful synthesis of Au@PS‐OH substrate and the uniform distribution of gold nanoparticles on the substrate surface. The SERS substrate revealed good selectivity and reproducibility with an enhancement factor of 2.6×10 4 . Finally, an analytical method for the determination of nitrofurantoin in cosmetics was established by SERS using Au@PS‐OH substrate coupling with efficient sample preparation process. It was satisfied that trace nitrofurantoin could be actually detected and quantified to be 1.77 and 7.74 mg/L in a mouthwash and rose‐mist sample, respectively, with good recoveries of 86.8‐106% and relative standard deviations of 0.9‐2.9%. The comparable analytical results for real samples were achieved by the traditional high‐performance liquid chromatography (HPLC) method, which validated the reliability of the proposed method. It is expected that this SERS method has great potential for the rapid and on‐site analysis of trace additives in cosmetics. Abstract : An accurate SERS method was developed for the rapid analysis of a trace banned antibiotic, nitrofurantoin, in various cosmetics by use of Au@PS‐OH substrate. The substate possessed the uniform distribution of gold nanoparticles on the substrate surface, resulting in appropriate "hot spots" and further good analytical sensitivity. Moreover, the proposed SERS method showed good selectivity and reproducibility to the trace nitrofurantoin in cosmetics.